Spectacle dominance and the existential vacuum: a critical reflection on the age of the spectacle in DeLillo’s The silence - Liu, Haijie; Wang, Ting (Frontiers in Communication, 2026)
This paper employs Guy Debord’s theory of the society of the spectacle as its core framework, integrating Jean Baudrillard’s consumer society and Byung-Chul Han’s critique of digital culture, among other perspectives, to conduct a systematic interpretation of Don DeLillo’s novel The Silence. The study demonstrates that through the extreme scenario of a global digital system collapse, the novel profoundly reveals the operational logic and existential consequences of the society of the spectacle in the contemporary era. Despite the spectacle’s attempt to erase all authentic experience, DeLillo offers replicable paths of resistance through Tessa’s “embodied documentation” and Martin’s “intellectual defiance.” The paper contends that The Silence not only serves as a powerful testing ground for the society of the spectacle but also expands its theoretical boundaries, offering new interpretive possibilities for understanding the “post-spectacle” phenomenon.